I'm a bit confused about the following statement from a script. We look at the power series with coefficient $ a_k = (1+1/k)^{k^2}$ and want to compute the radius of convergence $R$ of the series. The solution given is $R=1$, applying the $k^2$ root to $a_k$. I don't get this: The Cauchy-Hadamard formula involves the $k$th root which would give $R=1/e$ in my opinion. Is this a mistake in the script or is it me who is mistaken?

  • 1
    You are correct; it's likely a typo. – T. Bongers Dec 7 at 1:16
  • 1
    You do not say what power series actually is. If it is $$\sum (1+1/k)^{k^2}\;x^{k^2}$$ then you should use the $k^2$ root. – GEdgar Dec 7 at 12:16

You are indeed correct.

For coefficients $a_k:=(1+\frac {1}{k})^{k^2}$, the Cauchy-Hadamard formula gives:

$$R=\frac {1}{\limsup_{k\to\infty}(|a_k|)^{\frac {1}{k}}}=\frac {1}{\limsup_{k\to\infty}(|(1+\frac {1}{k})^{k^2}|)^{\frac {1}{k}}}=\frac {1}{\limsup_{k\to\infty}((1+\frac {1}{k})^{k^2})^{\frac {1}{k}}}=\frac {1}{\limsup_{k\to\infty}(1+\frac {1}{k})^k}=\frac {1}{e}$$

Just another way to do it. $$a_k=(1+\frac {1}{k})^{k^2}\implies \log(a_k)=k^2\log \left(1+\frac{1}{k}\right)$$ $$\log(a_k)-\log(a_{k+1})=k^2\log \left(1+\frac{1}{k}\right)-(k+1)^2\log \left(1+\frac{1}{k+1}\right)$$ Now, use Taylor expansions to get $$\log(a_k)-\log(a_{k+1})=-1+\frac{1}{3 k^2}+O\left(\frac{1}{k^3}\right)$$ Continue with Taylor $$\frac{a_k} {a_{k+1}}=\frac{1}{e}+\frac{1}{3 e k^2}+O\left(\frac{1}{k^3}\right)$$ making $R=\frac{1}{e}$ as you found.

Your Answer

By clicking "Post Your Answer", you acknowledge that you have read our updated terms of service, privacy policy and cookie policy, and that your continued use of the website is subject to these policies.

Not the answer you're looking for? Browse other questions tagged or ask your own question.